Correlation of neurologic dysfunction with CT findings in early acute stroke. - Scott, J; Buchan, A; Sevick, R (1999)
OBJECTIVE: To determine the frequency of early computed tomographic (CT) findings of ischemia and their relationship to symptom duration and neurologic dysfunction within 3 hours of ischemic stroke. METHODS: The CT scans of 39 acute stroke patients were evaluated for signs of early ischemic change within 3 hours of symptom onset and without knowledge of the patient's neurologic deficit or results of a 24 hour follow-up post-thrombolysis CT. Early CT signs of acute ischemic change or thromboembolism were hypoattenuation of the insular ribbon, obscuration of the lentiform nucleus, cortical hypodensity/effacement, and hyperdense middle cerebral artery sign. RESULTS: Signs of acute ischemic change were seen on the baseline scan in 25/39 patients (64%). Hypoattenuation of the insular ribbon was seen in 11 patients, obscuration of the lentiform nucleus in 13, cortical hypodensity/effacement in 13, and hyperdense middle cerebral artery sign in 7. The prevalence of early ischemic signs was directly associated with increasing neurologic disability at the time of presentation. No clear relationship existed between symptom duration and the presence of CT signs. CONCLUSIONS: Evidence of cerebral ischemia is frequently seen on CT within 3 hours of symptom onset. The degree of neurologic disability correlates with CT signs of ischemia.